(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. Monosodium Glutamate is one of the most world’s most widely used food additives. Its toxic effect have been shown in numerous animal studies, in which study MSG effects on cardiovascular system, therefore, This study was aimed to investigate the effect of alpha lipoic acid(ALA) on the damage in the large blood vessels induce by Mono sodium glutamate. Thirty two male rabbits was divided equally and randomly into four groups as following. Control group in which rabbits where fed with normal diet without supplementation, second group was gived MSG orally (8mg/kg.BW), While animals of third group were given ALA orally (60mg/kg.BW) while animal in fourth group were given orally (MSG 8mg/kg.bw and ALA 60mg/kg.bw), all treatment are extended to 8 weeks. The outcomes of research revealed a significant increased (p<0.05) in aortic medial layer thickness in animals administration of MSG in a comparesion with control and groups treated and distortion structure of laminar fibers, endothelial cells lost normal squamous. In addition, there is a significant decreased (p<0.05) in medial tunica thicken in animals used ALA combination with MSG, so we noted return the disarranged of architecture tissue near.